Anoxygenic phototroph pufLM gene sequences derived from tropical aquatic sampling sites: Diversity, distribution, and phylogenetics - Padilla Crespo, Elizabeth; Gordils, Lois; Ramirez, Xelimar; Michael Ceballos, Ruben (Access microbiology, 2020)
Purple sulfur bacteria (PSB) and purple non-sulfur bacteria (PNSB) are characterized by their ability to perform anoxygenic photosynthesis. PSB and PNSB are ubiquitously found in coastal waters, enclosed lagoons, stagnant water, mangrove soils, estuaries, and similar environments. In this study, we examine microbial diversity in PSB enrichments derived from a variety of tropical sampling sites (e.g., Thailand, Puerto Rico) associated with shrimp ponds, coastal mangroves, fresh water ponds, and Nymphaeaceae (i.e., water lily) plant tissue. Since 16S rRNA-based analyses are inadequate to describe the diversity of phototrophic bacteria, other biomarkers (e.g., pufLM) are used to construct phylogenies and elucidate biogeography. Our samples indicate that the majority of sequences associated with freshwater pond PSB were related to known marine, halophilic, or salt-tolerant PSB (e.g., Marichromatium, Allochromatium, Thiococcus, and Thiohalocapsa). Phylotypes not closely-associated with known species of PSB (or PNSB) were also found. PNSB gene sequences, which appear to be related to Rhodopseudomonas and Rhodoplanes, were mostly found in freshwater samples and from Nymphaeaceae plant tissues, suggesting a difference in the ecology and distribution of these two broader bacterial groups. This difference is likely due to differences in habitat such as physical (e.g., temperature) and chemical parameters (e.g., salinity). Our preliminary analyses demonstrate a rich diversity of anoxygenic phototrophic bacteria from tropical sampling sites. Few studies have described the diversity of purple bacteria in tropical environments using full pufLM gene sequences. Employing next-generation sequencing (NGS) appears to provide greater resolution towards a deeper understanding of the global diversity and distribution of these anoxygenic phototrophs.